2014
DOI: 10.1016/j.ijporl.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Common genes for non-syndromic deafness are uncommon in sub-Saharan Africa: A report from Nigeria

Abstract: INTRODUCTION Little is known about the molecular epidemiology of deafness in sub-Saharan Africa (SSA). Even in Nigeria, the most populous African nation, no genetic studies of deafness have been conducted. This pioneering work aims at investigating the frequencies of gene mutations relatively common in other parts of the world (i.e. those in GJB2, GJB6, and mitochondrial DNA) among subjects from Nigeria with hearing loss (HL) with no evidence of acquired pathology or syndromic findings. In addition, we review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 36 publications
2
22
2
Order By: Relevance
“…Apart from the Ghanaian population, where the GJB2 founder mutation p.R143W (c.427C>T) was shown to be highly prevalent [17] and implicated in approximately 25% of familial cases and 8% of isolated cases of HI [18], our study is consistent with previous reports in other populations of African descent [68,69]. Mutations in GJB6, including the 342-kb deletion, GJB6-D13S1830, were not reported in cohorts of 182, 44 and 401 probands from South Africa, Nigeria and Ghana, respectively [18,69,70]. As in the Cameroonian population, disease-causing mutations in GJB2 are also less prevalent or absent in populations from Kenya, Sudan, Uganda, Nigeria, Mauritania and South Africa [5,33,[69][70][71][72].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Apart from the Ghanaian population, where the GJB2 founder mutation p.R143W (c.427C>T) was shown to be highly prevalent [17] and implicated in approximately 25% of familial cases and 8% of isolated cases of HI [18], our study is consistent with previous reports in other populations of African descent [68,69]. Mutations in GJB6, including the 342-kb deletion, GJB6-D13S1830, were not reported in cohorts of 182, 44 and 401 probands from South Africa, Nigeria and Ghana, respectively [18,69,70]. As in the Cameroonian population, disease-causing mutations in GJB2 are also less prevalent or absent in populations from Kenya, Sudan, Uganda, Nigeria, Mauritania and South Africa [5,33,[69][70][71][72].…”
Section: Discussionsupporting
confidence: 91%
“…Mutations in GJB6, including the 342-kb deletion, GJB6-D13S1830, were not reported in cohorts of 182, 44 and 401 probands from South Africa, Nigeria and Ghana, respectively [18,69,70]. As in the Cameroonian population, disease-causing mutations in GJB2 are also less prevalent or absent in populations from Kenya, Sudan, Uganda, Nigeria, Mauritania and South Africa [5,33,[69][70][71][72].…”
Section: Discussionmentioning
confidence: 93%
“…Other studies have shown differences in genes coding for deafness in certain ethnic minorities [16][17][18][19][20]. Alternative explanations could be infections, prematurity, and neonatal complications [21], but this is less likely in view of the evenly distributed comorbidity in the present study.…”
Section: Incidence Rate Of Cochlear Implant Versus Ethnicitycontrasting
confidence: 56%
“…The GJB6-D13S1830 deletion and the mitochondrial mutations were also not observed in this group (Kabahuma et al, 2011). GJB2 mutations were also absent among deaf probands from the Yoruba tribe residing in Ibadan, a suburban city in Nigeria (Lasisi et al, 2014). Similarly, an analysis of a large cohort of Ugandan deaf patients identified none of the common GJB2 deletions (Javidnia et al, 2014).…”
Section: Gjb2mentioning
confidence: 70%
“…Studies among African populations reported that pathologic GJB6 mutations have been widely screened but not identified. Specifically, they were found to be absent in African populations within South Africa (Kabahuma et al, 2011), Nigeria (Lasisi et al, 2014), Cameroon (Bosch et al, 2014), Brazil (Batissoco et al, 2009) and the United States Samanich et al, 2007).…”
Section: Gjb6mentioning
confidence: 99%